Between ambitions and realities: The pathway of European Development Cooperation since Maastricht - Simon Hartmann (Austrian Foundation for Development Research (ÖFSE), 2009)
As soon as with the Treaty of Maastricht, the newly founded European Union formally stated a broad development cooperation approach in the supranational treaties. Since then the overall institutional framework has been continuously improved in favour of development cooperation by both, legal acts and 'soft law' while implementation of development policy issues mostly has lagged behind. Based on an evaluation of the changes on the institutional layer, the analysis will provide few selected evidence, that from a political view European development cooperation has failed to meet its rather high ambitions. – – Die Gründung der Europäischen Union im Jahr 1992 markiert den Zeitpunkt, an dem Entwicklungszusammenarbeit auf breiter Basis in den supranationalen Verträgen festgeschrieben wurde. Seither wurden die institutionellen Rahmenbedingungen durch Gesetzgebung und nicht rechtsverbindliche Übereinkünfte ('soft law') für Entwicklungszusammenarbeit auf europäischer Ebene fortwährend verbessert; die Umsetzung auf politischer Ebene wird diesem Prozess jedoch nicht ausreichend gerecht. Auf Basis einer Bewertung der institutionellen Veränderungen liefert die Analyse einige Belege dafür, dass die politische Umsetzung den ziemlich hohen Ansprüchen der europäischen Entwicklungszusammenarbeit bis heute nicht gerecht wurde.
Keywords: 330